Konsep Pendidikan (al-Ta’dib) untuk Membentuk Kepemimpinan Menurut al-Attas - Suhandi Suhandi (Fakultas Ushuluddin, Universitas Darussalam Gontor, 2020)
This research is try to find about relevation of education (ta’dib) concept which formulated by al-Attas as an alternative to poduce a good leadership. This research is qualitative research which used character study methodology, as well as used education philosophy, sufistic and lingusitic approach. This research is emphasize internal coherence method to analyzed data, that is understanding all of his concepts of thought based on relevance between one and the other, also establish the most basic of thought and the most central of topics. From this research, the author has discovered that ta’dib is mean instilled adab to human self. Then, leadership is trust from God, which will ask that responsibility. This leadership include two dimension, that is for individu (self) and collective (society). This leadership is based on justice, wisdom and adab, that justice is realization of adab, in the same manner as refelction of wisdom. Therefore, wisdom (hikmah), courtesy (adab) and justice (‘adl) must be instilled to form leadership. In the implementation of the ta'dib, there are also several things that must be considered: (1) emphasis on the soul, (2) integration between the knowledge of fardhu ‘ain and fardhu kifayah, and (3) dependence on authority. Beside that, in the implementation of the ta'dib, is use tawhid method.